KAPASITAS PERANGKAT DESA TELUK BAKAU KECAMATAN GUNUNG KIJANG DALAM MENGELOLA ALOKASI DANA DESA - Madiono, Imam; MUHAMMAD, ADJI SURADJI; Safitri, Dian Prima (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2016)
Village Government is the lowest administrative unit in the state governments that have given theright of indigenous autonomy with certain limits as a unified community law (adat) are entitled toregulate and manage the affairs of the local community in the implementation of the rule of origin.The success of an organization to meet the challenges set by people who do the work on it, so thecapacity of the individual must be considered. Considering there is a budget increase for the village,the village is required to develop the capacity to manage these budgets to the maximum. Thepurpose of this study is essentially to Know the capacity of Teluk Bakau manage Village FundAllocation. According to Law No. 6 Tahun2014 about the village in Article 72 paragraph (1) itemd, explained that the allocation of village funds that are part of the balance funds received byRegency / City. This study uses the theory Riyadi Soeprapto (Novita Sari, et al., 2014: 635) whosuggested that capacity building should be implemented in an effective and sustainable in three (3)levels: Level Individual, Organizational Levels, and Level System. Data analysis techniques usedin this research is qualitative descriptive analysis technique. After doing research, the final resultsof the study suggested that the Irish village of Teluk Bakau manage Village Allocation Fund, takinginto account the dimensions of capacity development are taken from the individual level, the level oforganization, as well as the systems level, overall there are no constraints or problem- a bigproblem that can inhibit the allocation of these funds. General Allocation Fund budget absorption,both in Shopping Indirect and direct expenditure amounted Rp.334.072.480, and absorbedamounted Rp.302.828.130 or approximately 90.6%. The problem that occurs is contained by thevillage which still provides maximum performance in carrying out its duties and functions as themanager of the Village Fund Allocation, this is because the device is that Village take office in thegovernment of Teluk Bakau, so mastery of tasks and functions are still not optimal.